(untitled) (Scientific journal of the Fergana State University, 2024)
This article presents the results of a study of the elemental composition of the above-ground and underground parts of celery (Apium Graveolens var. Dulce), considered one of the edible green crops, and soil samples from the region where it is found. The plant is grown and isolated. An Avio200 ISP - OES Inductively Coupled Plasma Optical Emission Spectrometer (Perkin Elmer, USA) was used for this purpose. It was observed that celery (Apium) plant contains 30 elements in its dried root, stem and soil, and 26 elements in its undried stem. Based on the obtained results, it was found that the amount of macroelements in the plant is much higher than microelements.